Determination of Metoclopramide with Chromium(III) Thiocyanate Complexes - Bratulescu, George (Asian Journal of Chemistry, 2015)
The determination of metoclopramide (4-amino-5-chloro-N-[(2-diethylamino)ethyl]-2-methoxybenzamide) has been achieved by means of gravimetric, oxidimetric and spectrometric methods. The experimental data proves that the methods are accurate enough and not affected by systematic errors.